2010
DOI: 10.1038/ja.2010.31
|View full text |Cite
|
Sign up to set email alerts
|

Caripyrin, a new inhibitor of infection-related morphogenesis in the rice blast fungus Magnaporthe oryzae

Abstract: Caripyrin (trans-5-(3-methyloxiranyl)pyridincarboxylic acid methyl ester, 1), a new pyridyloxirane, was isolated from submerged cultures of the basidiomycete Caripia montagnei. The compound was found to inhibit conidial germination and appressorium formation in the rice blast fungus Magnaporthe oryzae, whereas the infection-related morphogenesis in several other phytopathogenic fungi was not affected. In plant assays on rice, 1 was found to protect plants more efficiently against fungal infection than the stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Caripia montagnei ), was found to inhibit conidial germination and appressorium formation in P. oryzae without being cytotoxic, antibacterial and nematicidal (Rieger et al, 2010). Candida biofilm formation was reduced by 63–98% when sub-MIC levels of Boesenbergia pandurata (finger root) oil were used (Taweechaisupapong et al, 2010).…”
Section: New Ecologically Friendly Strategies To Manage Fungal Biofilmentioning
confidence: 99%
“…Caripia montagnei ), was found to inhibit conidial germination and appressorium formation in P. oryzae without being cytotoxic, antibacterial and nematicidal (Rieger et al, 2010). Candida biofilm formation was reduced by 63–98% when sub-MIC levels of Boesenbergia pandurata (finger root) oil were used (Taweechaisupapong et al, 2010).…”
Section: New Ecologically Friendly Strategies To Manage Fungal Biofilmentioning
confidence: 99%
“…In 2010 Rieger et al reported the flat structure of the fungal secondary metabolite (+)‐caripyrin ( 1 ; Figure 1), which they isolated from submerged cultures of the basidiomycete Caripia montagnei . The compound exhibits selective and strong inhibition of conidial germination in the rice blast fungus Magnaporthe oryzae , the causal agent of blast, a devastating disease in cultivated rice 1. However, the absolute configuration of its two stereogenic centers remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…13 The fungal strain IBWF-029-96 was identified as Penicillium sp. Its conidiophores showed all morphological characteristics of the genus as described.…”
Section: Biological Assaysmentioning
confidence: 99%
“…13 Seeds of Setaria italica, Lepidium sativum, O. sativa CO-39 and Triticum aestivum RIBAND were used. The assay was performed thrice.…”
Section: Biological Assaysmentioning
confidence: 99%
See 1 more Smart Citation